Electrochemical synthesis of ammonia directly from N2 and water over iron-based catalysts supported on activated carbon. Issue 1 (5th December 2016) - Cui, Baochen; Zhang, Jianhua; Liu, Shuzhi; Liu, Xianjun; Xiang, Wei; Liu, Longfei; Xin, Hongyu; Lefler, Matthew J.; Licht, Stuart
Abstract : A CO2 -free electrosynthesis of ammonia from air and water is presented with a solid Fe2 O3 catalyst confined to activated charcoal. Abstract : A new green methodology for the CO2 -free synthesis of ammonia from air and water is presented. The conventional production of H2 utilizes fossil fuels and causes a massive greenhouse gas release, making ammonia production one of the most energy intensive and highest CO2 emitting manufacturing processes. In 2014 we introduced an alternative method for efficient ammonia synthesis that utilizes water (along with N2 ) instead of H2 based on electrolysis of nano-structured catalyst suspensions of Fe2 O3 in low temperature aqueous or higher temperature molten hydroxide electrolytes. Here, this is replaced with a solid Fe2 O3 catalyst confined to activated charcoal opening pathways to improve the rate and efficiency of ammonia production. Cyclovoltammetric studies show that Fe2 O3 /AC catalysts can inhibit competing hydrogen reduction and enhance reduction of iron. This iron-based catalyst supported on activated carbon (Fe2 O3 /AC) was prepared for use as an electrocatalyst for the electrochemical synthesis of ammonia in molten hydroxide (NaOH–KOH) directly from wet N2 at atmospheric pressure. XRD analysis shows that the catalyst exhibits a Fe2 O3 structure. At 250 °C, a voltage of 1.55 V with a current density of 49 mA cm −2 yielded the highest rate of ammonia formation, 8.27 × 10 −9 mol (s cm 2 ) −1 . The highest coulombic efficiency for the 3e − per ammonia formation, 13.7%, was achieved at 1.15 V with a lower average current density of 11 mA cm −2 . This is a promising simple technology for the sustainable synthesis of ammonia in the future.